Primary hyperparathyroidism presenting as severe hypercalcemia with acute pancreatitis in pregnancy. (3rd May 2020) - Bansal, S.; Kaushik, R. M.; Kaushik, R.; Modi, S.; Raghuvanshi, S.; Kusum, A.
Abstract: Primary hyperparathyroidism presenting first time with severe hypercalcemia is rare in pregnancy. We report a case of primary hyperparathyroidism due to a cystic parathyroid adenoma presenting as severe hypercalcemia with acute pancreatitis in second trimester of pregnancy. Acute pancreatitis was managed by conservative treatment. Hypercalcemia failed to respond to medical management and ultimately responded to ultrasound-guided ethanol ablation of parathyroid adenoma. The delivery was uneventful and patient continues to remain normocalcemic during follow up. As such, ethanol ablation of parathyroid adenoma may be considered during pregnancy in case of failure of response to medical management and when surgical removal of parathyroid adenoma is not safe.